2020
DOI: 10.1016/j.apsb.2020.10.009
|View full text |Cite
|
Sign up to set email alerts
|

GSH-responsive SN38 dimer-loaded shape-transformable nanoparticles with iRGD for enhancing chemo-photodynamic therapy

Abstract: Accurate tumor targeting, deep penetration and superb retention are still the main pursuit of developing excellent nanomedicine. To achieve these requirements, a stepwise stimuli-responsive strategy was developed through co-administration tumor penetration peptide iRGD with shape-transformable and GSH-responsive SN38-dimer (d-SN38)-loaded nanoparticles (d-SN38@NPs/iRGD). Upon intravenous injection, d-SN38@NPs with high drug loading efficiency (33.92 ± 1.33%) could effectively accumulate and penetrate into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 58 publications
1
35
0
Order By: Relevance
“…Besides, other characteristics of nanovaccine also influence its internalization by DCs, such as shape, flexibility, and roughness. [ 64b,106 ] Studying the uptake of different shapes of gold NPs (AuNPs) coated with West Nile virus envelope (E) protein revealed that rod AuNPs‐Es (40 × 10 nm) are taken up by bone‐marrow‐derived dendritic cells (BMDCs) than spherical (20 and 40 nm) or cubic (40 × 40 × 40 nm) AuNPs‐Es. [ 107 ] To assess the effects of surface roughness on internalization by DCs, PLGA microspheres (MS) with different degrees of surface roughness were prepared by coating with cancer cell‐derived vesicles (VE) to modulate their surface topology.…”
Section: Nanovaccine‐based Strategies To Overcome Ldimp Cascadementioning
confidence: 99%
“…Besides, other characteristics of nanovaccine also influence its internalization by DCs, such as shape, flexibility, and roughness. [ 64b,106 ] Studying the uptake of different shapes of gold NPs (AuNPs) coated with West Nile virus envelope (E) protein revealed that rod AuNPs‐Es (40 × 10 nm) are taken up by bone‐marrow‐derived dendritic cells (BMDCs) than spherical (20 and 40 nm) or cubic (40 × 40 × 40 nm) AuNPs‐Es. [ 107 ] To assess the effects of surface roughness on internalization by DCs, PLGA microspheres (MS) with different degrees of surface roughness were prepared by coating with cancer cell‐derived vesicles (VE) to modulate their surface topology.…”
Section: Nanovaccine‐based Strategies To Overcome Ldimp Cascadementioning
confidence: 99%
“…To address this issue, it is desirable to maintain the integrity of the drug during blood circulation and achieve specific and rapid release at the target site. [45,46] Thus, azido-GFLG-GEM was prepared to avoid the metabolism of GEM, as shown in Scheme S2 , Supporting Information. In addition, the tetra-peptide sequence (GFLG) is a substrate of cathepsin B.…”
Section: Design and Preparation Of Amphiphilic Pegylated Dendron-gflg-gem Prodrugs (Pdps)mentioning
confidence: 99%
“…The most effective way to combat ROS in cells is to reduce such peroxides using glutathione (GSH). Many studies have reported that the level of GSH in tumours is much higher than that in normal tissues (YANG et al, 2019;LIN et al, 2020). This may be one of the reasons for their strong adaptability and an unfavourable factor for PDT in the treatment of CCA.…”
Section: Introductionmentioning
confidence: 99%